The Influence of β‐diiminato Ligands on As4 Activation by Cobalt Complexes. Issue 28 (8th June 2018) - Spitzer, Fabian; Balázs, Gábor; Graßl, Christian; Keilwerth, Martin; Meyer, Karsten; Scheer, Manfred
Abstract: In a systematic study of the activation of As4, three [LCo(tol)] (L=β‐diiminato) complexes have revealed different steric and electronic influences. 2, 6‐Diisopropylphenyl (Dipp) and 2, 6‐dimethylphenyl (dmp) flanking groups were used, one of the ligands with H backbone substituents (β‐dialdiminate L 0 ) and two with Me substituents (β‐diketiminates L 3 and L 1 ). In the reaction with As4, different dinuclear products [(LCo)2 As4 ] (LM=L 0 (1 ), L 1 (2 ), L 3 (3 )) were isolated, with all showing differently shaped [Co2 As4 ] cores in the solid state: octahedral in 1, prismatic in 2, and asterane‐like in 3 . Thermal treatment of 3 leads to the abstraction of one arsenic atom to yield [(L 3 Co)2 As3 ] (4 ). All products were comprehensively characterized by single‐crystal X‐ray diffraction, FD‐MS, and 1 H NMR spectroscopy. A rational explanation for the different reactivity is also proposed and DFT calculations shed light on the nature of the highly flexible [Co2 As4 ] cores. Abstract : Core business : Yellow arsenic was reacted with three different β‐diiminato complexes of Co. The geometry of each individual As4 core in the resulting dinuclear [(LCo)2 As4 ] complexes depends on the β‐diiminato ligand used, which differ in their aromatic flanking groups and α‐substituents. Moreover, the extrusion of one As atom and the formation of [(L 3 Co)2 As3 ] were accomplished under thermolytic conditions.